The Legitimacy of Qurbani Fiqhiyyah in the Name of Institutions: A Comparative Analysis between the Views of Classical and Contemporary Scholars - Aha Putra, Ahmad Fakk Dominika Taqi; Afkari, Najmi Nahdin; Umur, Muhammad Ma’aliyal; Nulinnaja, Ratna; Aha Putra, Kivah; Aha Putra, J. Nabiel (Bahasa Indonesia, Bahasa English, 2025)
This study discusses the legal legitimacy of the implementation of qurbani on behalf of institutions in the perspective of classical and contemporary fiqh and its relevance in the modern socio-religious context. The background of the research departs from the increasing practice of qurbani carried out by government, educational, and corporate institutions as a religious expression as well as a form of social concern. However, this practice raises juridical-theological issues related to the legitimacy of the institution as a perpetrator of qurbah worship which in shari’i requires the intention and ownership of the mukallaf individual. This study uses a qualitative approach with a literature study design through normative-theological and juridical-comparative analysis of primary sources in the form of verses, hadiths, and classical fiqh texts, and secondary sources in the form of contemporary literature and fatwas. The results of the study show that classical fiqh provides limited legitimacy for imams or leaders to perform qurbani on behalf of the ummah using public funds, while the contemporary view emphasizes that institutions are not the subject of mukallaf so they cannot become qurbani perpetrators independently. Thus, qurbani on behalf of the institution is only valid if the institution acts as a representative who distributes individual qurbani or mukallaf groups, while the use of institutional funds without determining the name of the sacrificer is classified as collective alms, not sharia qurban.